2018
DOI: 10.1177/1076029618779136
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variability in Selected Genes in Patients With Deep Vein Thrombosis and Platelet Hyperaggregability

Abstract: The aim of this study was to evaluate the genetic variability of the selected single nucleotide polymorphisms (SNPs) and examine the association between these SNPs and risk for deep vein thrombosis (DVT) in patients with sticky platelet syndrome (SPS). We examined 84 patients with SPS and history of DVT and 101 healthy individuals. We were interested in 2 SNPs within platelet endothelial aggregation receptor 1 (PEAR1) gene (rs12041331 and rs12566888), 2 SNPs within mkurine retrovirus integration site 1 gene (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
(21 reference statements)
2
20
0
Order By: Relevance
“…These were located in different genes related to platelet functional receptors, regulators of cytoskeleton and signaling proteins. Among these genes, the following were described: MIR100HG , MME , PIP3-E , GLIS3 , LDHAL6A , ANKS1B , PIK3CG , MAGI1 , C8orf86 , FGFR1 , LPAR1 , CACNB2 , SLC39A12 , RPP25 , SCAMP5 , BMPR1A (revisited in Bunimov et al [19]), ANKRD26 [20], pannexin [21], ADRA2 [22] and the most relevant PEAR-1 [22,23,24]. Notably, none of these genetic variants was found in the ABO locus.…”
Section: Resultsmentioning
confidence: 99%
“…These were located in different genes related to platelet functional receptors, regulators of cytoskeleton and signaling proteins. Among these genes, the following were described: MIR100HG , MME , PIP3-E , GLIS3 , LDHAL6A , ANKS1B , PIK3CG , MAGI1 , C8orf86 , FGFR1 , LPAR1 , CACNB2 , SLC39A12 , RPP25 , SCAMP5 , BMPR1A (revisited in Bunimov et al [19]), ANKRD26 [20], pannexin [21], ADRA2 [22] and the most relevant PEAR-1 [22,23,24]. Notably, none of these genetic variants was found in the ABO locus.…”
Section: Resultsmentioning
confidence: 99%
“…Based on PEAR1 genotype, they observed significantly different ADP‐induced platelet aggregation (29.1, 25.4, and 22.9 for genotypes GG, GA, and AA, respectively, P = 0.0005) and detected differences in the 30‐day incidence of a composite cardiovascular phenotype consisting of cardiovascular death, nonfatal myocardial infarction, and ischemic stroke (HR = 2.78, 95% CI 1.13–6.82, P = 0.03). Positive associations with deep vein thrombosis in those with sticky platelet syndrome as well as coronary artery aneurysm in individuals with Kawasaki disease have also been shown by PEAR1 rs12041331 genotype 33,34 …”
Section: Discussionmentioning
confidence: 93%
“…Positive associations with deep vein thrombosis in those with sticky platelet syndrome as well as coronary artery aneurysm in individuals with Kawasaki disease have also been shown by PEAR1 rs12041331 genotype. 33,34 Further studies have suggested a genotype x aspirin interaction exists whereby aspirin-treated carriers of rs12041331 minor (A) allele have enhanced risk of experiencing a clinical event compared with carriers of the same allele who are not treated with aspirin. 29 Specifically, it was observed in patients with stable coronary artery disease of European descent that rs12041331 A-allele carriers treated with aspirin have significantly increased risk of myocardial infarction (odds ratio (OR) = 2.08, 95% CI 1.01-4.09, P = 0.048) compared with those who were not exposed to aspirin (OR = 0.25, 95% CI 0.03-2.03, P = 0.19).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Genetic variations may also be an important risk factor protecting or predisposing some people to VTE in winter. 28 It seems that the combination of inflammation, the amount of decreased temperature, genetic factors, age, and acute infections in winter and their interaction are important in predisposing some people to VTE during winter.…”
Section: Seasonal Variation Of Vte According To the Region Of Studymentioning
confidence: 99%